Landslides Risk Analysis and Sustainable Disaster Management - Sassa, Kyoji; Fukuoka, Hiroshi; Wang, Fawu; Wang, Gonghui (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Based on contributions to the first General Assembly of the International Consortium on Landslides, this reference and status report emphasizes the mechanisms of different types of landslides, landslide risk analysis, and sustainable disaster management. It comprises the achievements of the ICL over the past three years, since the Kyoto assembly. It consists of three parts: research results of the International Programme on Landslides (IPL); contributions on landslide risk analysis; and articles on sustainable disaster management. In addition, the history of the ICL activities (under the support of UNESCO, WMO, FAO, UN/ISDR, and UNU) is recounted to create a comprehensive overview of international activity on landslides. The contributions reflect a wide range of topics and concerns, randing from field studies, identification of objects of cultural heritage at landslide risk, as well as landslide countermeasures.